0.06-0.03(x+1)=0.01(1-x)

Simple and best practice solution for 0.06-0.03(x+1)=0.01(1-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.06-0.03(x+1)=0.01(1-x) equation:


Simplifying
0.06 + -0.03(x + 1) = 0.01(1 + -1x)

Reorder the terms:
0.06 + -0.03(1 + x) = 0.01(1 + -1x)
0.06 + (1 * -0.03 + x * -0.03) = 0.01(1 + -1x)
0.06 + (-0.03 + -0.03x) = 0.01(1 + -1x)

Combine like terms: 0.06 + -0.03 = 0.03
0.03 + -0.03x = 0.01(1 + -1x)
0.03 + -0.03x = (1 * 0.01 + -1x * 0.01)
0.03 + -0.03x = (0.01 + -0.01x)

Solving
0.03 + -0.03x = 0.01 + -0.01x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.01x' to each side of the equation.
0.03 + -0.03x + 0.01x = 0.01 + -0.01x + 0.01x

Combine like terms: -0.03x + 0.01x = -0.02x
0.03 + -0.02x = 0.01 + -0.01x + 0.01x

Combine like terms: -0.01x + 0.01x = 0.00
0.03 + -0.02x = 0.01 + 0.00
0.03 + -0.02x = 0.01

Add '-0.03' to each side of the equation.
0.03 + -0.03 + -0.02x = 0.01 + -0.03

Combine like terms: 0.03 + -0.03 = 0.00
0.00 + -0.02x = 0.01 + -0.03
-0.02x = 0.01 + -0.03

Combine like terms: 0.01 + -0.03 = -0.02
-0.02x = -0.02

Divide each side by '-0.02'.
x = 1

Simplifying
x = 1

See similar equations:

| 7(5m+7(n+8p))+2n= | | 11x^2+7x-10=5 | | 4(y+8)=-32+4y | | -16x^2+32x-80=0 | | 4+3(p-2)=64 | | 2x-5-11x-8= | | (u^2)(-6uv^2)= | | 2x+9=12x-81 | | 38-a*11=34 | | 10x-61=18y+5 | | 10+5(x-2)=7a+15 | | 3(8a-9)=33 | | 6x+4=9+-8 | | 24x^3-56x^2+9x-21=0 | | 6x-3-9=5x | | sqrt(2x+5)=2+sqrt(3x+5) | | 10x-110=180 | | x*3+4=10 | | 28y^6x+35xy= | | y=.005(150)+b | | 4xy=75 | | 4v^2-8v=11 | | sqrt(5-x)+sqrt(x-6)=x | | 4x+13-2x=7+5x-6 | | 11=7+2x^2 | | -5x-8x*5=0 | | 3sin^2x+5cosx-1=0 | | x*9=144 | | 3x+2x*3=-18 | | 2y-3x+9z=3 | | 4(4+v)+32v=11v | | 7x-5.28=-0.45 |

Equations solver categories